Modeling of river bed deformation composed of frozen sediments with increasing environmental temperature - E. I. Debolskaya; V. K. Debolsky; I. I. Grtsuk; O. YA. Maslikova; D. N. Ionov (Лëд и снег, 2015)
This paper is devoted to investigation of the influence of river flow and of the temperature rise on the deformation of the coastal slopes composed of permafrost with the inclusion of ice layer. The method of investigation is the laboratory and mathematical modeling. The laboratory experiments have shown that an increase in water and air temperature changes in a laboratory analogue of permafrost causes deformation of the channel even without wave action, i.e. at steady-state flow and non-erosive water flow velocity. The previously developed model of the bed deformation was improved to account for long-term changes of soil structure with increasing temperature. The three-dimensional mathematical model of coastal slopes thermoerosion of the rivers flowing in permafrost regions, and its verification was based on the results of laboratory experiments conducted in the hydraulic tray. Analysis of the results of mathematical and laboratory modeling showed that bed deformation of the rivers flowing in the permafrost zone, significantly different from the deformation of channels composed of soils not susceptible to the influence of the phase transition «water-ice», and can occur even under the non-erosive velocity of the water flow.